Heteronormativity and the Justification of Gender Hierarchy: Investigating the Archival Data From 16 European Countries - Ferrari, Federico; Imperato, Chiara; Mancini, Tiziana (Frontiers in Psychology, 2021)
Within the frame of System Justification Theory (Jost & Banaji, 1994), this study tested on archival data from 16 European Countries the general hypothesis that homonegativity, as an expression of gender binarism and heteronormativity, works as a legitimizing myth of gender hierarchy. Specifically, we hypothesized that 1. system justification would positively relate to homonegativity, and 2. this relation would depend on the country level of gender hierarchy, 3. on respondents’ gender, and 4. on the interaction between gender hierarchy and gender. We selected Gender Equality Index (GEI) as indicator of country system’s gender hierarchy, and items from European Social Survey-Round 9 (ESS-9) as indicators of respondents’ gender and levels of system justification and homonegativity. Hierarchical Linear Models partially confirmed hypotheses, suggesting homonegativity to work as a blatant prejudice and being more viable as a legitimizing myth in females from countries with higher gender hierarchy and in males from more gender equal countries. In both cases, homonegativity serves as a myth to justify participants’ ontological premise that the world is fair, and to counteract cognitive dissonance generated by the perception of a gender unequal system (in the case of woman) or by the perception of a gender equal system that can threaten gender privileges (in the case of man).